Pathological Fracture of Multiple Myeloma with CRAB Criteria: A Case Report - Burahman, Habib; Sifa, Silvia Laelatus; Asmara, Tabitha Puspaning (Media Publikasi Cendekia Indonesia, 2024)
Multiple myeloma (MM) is a malignancy of plasma cells, often preceded by an asymptomatic condition known as the precursor state of monoclonal gammopathy of undetermined significance (MGUS). The diagnosis of multiple myeloma is typically confirmed using the CRAB criteria, which include hypercalcemia, renal impairment characterized by elevated serum urea and creatinine levels, anemia, and bone abnormalities. We report a rare case of multiple myeloma in a 63-year-old male patient who presented with pain in his left hand following a fall against a wall. Clinical and radiological examinations revealed findings consistent with multiple myeloma, with a differential diagnosis including metabolic bone disease and metastatic bone disease